Pengaruh Kualitas Pelayanan Terhadap Kepuasaan Pelanggan(Studi Kasus Pada Bengkel Mobil Montecarlo Group Surakarta) - Putra damara, Sandy; , Nur Ahmad, S.E., M.Si (2015)
The aim in this study was to analyze the effect of tangible, reliabilty, responsiveness, assurance, empathy towards satisfaction Pelannggan on Car Repair Montecarlo Group of Surakarta. Analyze the Quality of Service (tangible, reliability, responsiveness, assurance, empathy towards customer satisfaction at Montecarlo Car Repair Group of Surakarta. The population in this study are all consumers who use the services in Montecarlo Car Repair Group of Surakarta, while the samples used by 50 respondents. The sampling technique used is the Convenience Sampling. The analysis tool used is normality test, multicollinearity, heteroscedasticity test, test the coefficient of determination (R2), F test (Test Accuracy Model) and t test (Test of Hypothesis). Based on the results of data analysis known variables are not tangible and not significant positive effect on customer satisfaction, which means that the lower the consumers' perception of tangible value, the more weak urge consumers to conduct customer satisfaction. Variable reliability no positive effect and no significant effect on customer satisfaction, which means that the lower the value of consumer perceptions of reliability, it will be increasingly weaker urge consumers to conduct customer satisfaction. Variable responsiveness and no significant positive effect on customer satisfaction, meaning that the higher the value of consumers' perception of responsiveness, the more powerful the urge consumers to conduct customer satisfaction. No assurance variables and no significant positive effect on customer satisfaction, which means that the lower the value of consumers' perception of assurance, it will be increasingly weaker urge consumers to conduct customer satisfaction. Empahty variables and no significant positive effect on customer satisfaction, which means that the steeper the value of consumers' perception of assurance, the more powerful the urge consumers to make satisfaction pelangganNilai R square (R2) obtained at 0.205. This means that the variation of the variable changes in the purchasing decision can be explained by tangible variables (X1), reliability (X2), responsiveness (X3), assurance (X4) and empathy (X5) of 20.5%. While the remaining 79.5% is explained or influenced by external factors other than the independent variables in the regression.